2017
DOI: 10.1111/hepr.12898
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of sofosbuvir/ledipasvir in patients with chronic hepatitis C genotype 1 with and without prior daclatasvir/asunaprevir therapy

Abstract: Prior DCV/ASV therapy is associated with failure of SOF/LDV therapy due to multiple RAVs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…This might be the reason for the different SVR rates between cirrhotic and non-cirrhotic patients (Figure 1b), since a previous study [23] showed that the NS5A RAVs lead to lower SVR12 in patient with cirrhosis. Recent reports demonstrated that the SVR rate was only 69% when treated with ledipasvir plus sofosbuvir therapy in patients with prior asunaprevir plus daclatasvir treatment [24]. Prior asunaprevir plus daclatasvir treatment is associated with failure of ledipasvir plus sofosbuvir therapy due to multiple HCV NS5A RAVs.…”
Section: Discussionmentioning
confidence: 99%
“…This might be the reason for the different SVR rates between cirrhotic and non-cirrhotic patients (Figure 1b), since a previous study [23] showed that the NS5A RAVs lead to lower SVR12 in patient with cirrhosis. Recent reports demonstrated that the SVR rate was only 69% when treated with ledipasvir plus sofosbuvir therapy in patients with prior asunaprevir plus daclatasvir treatment [24]. Prior asunaprevir plus daclatasvir treatment is associated with failure of ledipasvir plus sofosbuvir therapy due to multiple HCV NS5A RAVs.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the leading cause of death in patients with chronic hepatitis C. In recent years, direct‐acting antiviral (DAA) treatment has enabled many patients to achieve sustained virological responses (SVR) . Thus, it is expected that the development of HCC will be suppressed .…”
Section: Introductionmentioning
confidence: 99%
“…Also, Iio et al . reported that an SVR was achieved in 18 of 26 patients (69.2%) with virologic failure during and after DCV/ASV therapy . In contrast, Suda et al .…”
Section: Discussionmentioning
confidence: 92%